PHYSIOTHERAPY MANAGEMENT IN CASES OF POST OPEN REDUCTION INTERNAL FIXATION (ORIF) ON FRACTURE PATELLA SINISTRA IN RS UNS SURAKARTA WARD: CASE STUDY - Wulandari, Puput; Fatmarizka, Tiara (CV. Fahr Publishing, 2025)
Fracture of the patella is a relatively rare injury but has a significant impact on the function of the extensor mechanism in the human knee, especially if there is a significant dislocation or displacement of bone fragments in the knee. Surgical treatment using the Open Reduction and Internal Fixation (ORIF) method is the main choice to ensure optimal bone union and is used as a restoration of joint function in the knee. Open Reduction and Internal Fixation (ORIF) aims to restore the anatomical position of the patella and to ensure the stability of the knee structure. After ORIF installation, patients will often face disorders such as; pain, limitations in the range of joint motion (LGS), and decreased muscle strength. Physiotherapy plays an important role in dealing with these problems. This study aims to evaluate the effectiveness of physiotherapy interventions including ankle pump, quadriceps static contraction, breathing exercise, and early mobilization on improving knee function in patients with Post Open Reduction and Internal Fixation (ORIF) Fracture Patella. This study used a qualitative descriptive study design with a case study approach. The pain scale measured using the Numeric Rating Scale before the intervention was 8 after the intervention became 6. The range of motion of the joints was measured using a goniometer, and functional ability was measured using the lower extremity functional scale. Physiotherapy interventions including ankle pump, quadriceps static contraction, breathing exercise, and early mobilization have a positive effect on Post ORIF Fracture Patella patients.